Environmental factors associated with southern brown shrimp (Penaeus subtilis) yield at Brazilian Amazon coast (Ocean and Coastal Research, 2022)
We evaluated the relationship between southern brown shrimp Penaeus subtilis (Pérez Farfante, 1967) yield and environmental parameters on the Amazon continental shelf. We analysed monthly fishing effort data (number of days spent at sea) and yield (kg of tails) collected between 1978 and 2009. A causal relationship had been expected between Amazon River discharge during the main period of shrimp occurrence in estuarine waters (considering post larval settlement and juvenile recruitment in second semester of each year) and adult abundance (represented by fishery yield in the first semester of the following year). We detected significant correlations between monthly river discharge and yield with a negative lag of four months, and between river discharge during the dry season (June to November) and yield in the following year. In general, low and high discharges during a given year were associated with high and low fishery yields, respectively, during the following year.